THE LEGAL NATURE OF THE PREAMBLE OF THE CONSTITUTION - Simović, Darko Z (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Although an integral part of most constitutions, the preamble has for a long time been on the margin of interest of legal studies. The key reason for this is the fact that the legal nature of the preamble has still not been defined. To define it legal nature is a particularly delicate task, as it is a phenomenon which is at the junction between politics and law. In legal theory, there have emerged three perspectives regarding the legal nature of preamble whose legal effect is not established by the constitution itself. According to the first point of view, a preamble is a ceremonial political declaration and introductory statement into the normative part of the constitution, because of which it lacks the operative legal value. The second point of view attributes limited legal significance to the preamble but only as a tool for interpreting unclear constitutional norms, as it classifies them into a relevant socio-political context. According to the third point of view, the preamble is an integral part of the constitution and its legal effect is equal to the normative part of the constitution. The author suggests that any principal viewpoints and extremes should be avoided in drawing conclusions in this field, because the legal nature of the preamble first and foremost depends on its content.